2021
DOI: 10.1002/jmri.27828
|View full text |Cite
|
Sign up to set email alerts
|

DWI and IVIM Imaging in a Murine Model of Rhabdomyosarcoma: Correlations with Quantitative Histopathologic Features

Abstract: Background High cellularity and abnormal interstitial structures are some of the unfavorable factors that affect the treatment outcomes and survival of rhabdomyosarcoma (RMS) patients. Purpose To explore the correlation between diffusion‐weighted imaging (DWI) and intravoxel incoherent motion (IVIM) with quantitative histopathologic features in a murine model of RMS. Study Type Prospective. Animal Model Murine model of RMS (31 female BALB/c nude mice). Field Strength/Sequence 3.0 T; fast spin‐echo (FSE) T1‐wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Possible reasons are the inclusion of multiple cancer subtypes, the use of different MRI scanners, and the fact that ADC measurements are not currently standardized 30,31 . In our study, ADC values were moderately positively correlated with RSG and differed significantly between high and low reactive stroma groups, in line with the findings of most articles 14,26–28,32,33 …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Possible reasons are the inclusion of multiple cancer subtypes, the use of different MRI scanners, and the fact that ADC measurements are not currently standardized 30,31 . In our study, ADC values were moderately positively correlated with RSG and differed significantly between high and low reactive stroma groups, in line with the findings of most articles 14,26–28,32,33 …”
Section: Discussionsupporting
confidence: 85%
“…Conventional DWI has been used to evaluate stromal proportions within rectal, esophageal, pancreatic, breast cancer, head and neck squamous cell carcinoma, and rhabdomyosarcoma content in varying degrees 14,26–31 . However, two studies of rectal and breast cancer showed no correlation between ADC values 30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, Doudou et al 27 compared 10 and 4 b value parameters and found that there was no significant difference between the 2 groups of parameters. In the study of Fang et al, the authors used the same value of b as in our study 28 …”
Section: Discussionmentioning
confidence: 99%
“…In the study of Fang et al, the authors used the same value of b as in our study. 28 Research investigating the correlation between ADC and HIF-1α expression has shown varying results in different types of tumors. In a study in hepatocellular carcinoma by Huang et al, 29 the ADC value showed a strong positive correlation with HIF-1α expression.…”
Section: Discussionmentioning
confidence: 99%